THEORETICAL BASIS OF ORGANIZING STUDENTS' LEARNING ACTIVITIES ON THE BASIS OF PERSONALLY-ORIENTED EDUCATION (American Journal of Business Management, Economics and Banking, 2024)
This article discusses the essence, didactic possibilities, main directions, principles, and peculiarities of a new view of the personality of the person.